Professor, does your university (want to) know what you are doing? - Smedsrød, Bård; Longva, Leif (Septentrio Conference Series, 2014)
To make sure that resources are used optimally in maximizing the production of graduates (bachelors, masters and PhDs) and research (scientific publications in various channels), universities are constantly intensifying and improving their ways of recording and counting the achievements of their scientific staff. Teaching hours and scientific papers are meticulously monitored, and administrative staff is increasingly occupied making sure that this registration results in a true and just picture of the way human resources are being spent, and reveal how the production system may become more effective. However, in addition to research and teaching, there are some rather important work tasks that we all agree are very important, but nevertheless goes under the radar of the university counting regimes: Reviewing tasks. The scientists at the university spend time (frequently a lot of time) doing reviewing work for free for scientific journals. Our scientists also spend a lot of time working as reviewers for national and international funding bodies and in a great number of committees to evaluate the quality of job applicants. And they serve as quality referees in advanced exams such as master and PhD dissertations. Most of these tasks are pivotal to the scientific society and the society in general, yet not realized by the university. The truth is that many of these tasks, which can only be carried out by merited scientists, exist only in a kind of shadow land at the universities. A recent survey presented in a master thesis at the University of Tromsø documented that 15-20.000 hours per year is spent by UoT scientists to work for free for scientifical journals (Maria Refsdal (2010): “Peer review at the University of Tromsø : a study of time spent on reviewing and researchers’ opinions on peer review”). Does the university take any interest in the fact that as much as 20.000 hours paid for by tax payers money is given away for free to the scientific journals who would not survive if it weren't for this work? The answer appears to be “no”. We believe that a key for academic institutions to regain control over the scholarly publishing regime and force it to change into an all true open access system, is to make sure that they take a major interest in the reviewing tasks carried out by scientists. Recently researchers across the world have started a boycott of the publisher Elsevier, and declaring they do not wish to publish in Elsevier’s journals, nor do any refereeing or editorial work for these journals (http://thecostofknowledge.com/). The boycot came about as a protest against the high subscription prices. An interesting question is: Does the University have any view on researchers’ boycotts like this? We claim that universities as employers and managers of public research funding, by taking interest in what their employees do and not do, the university may have a forceful tool to lead the publishing houses in directions as desired by the university and the society. Would a closer control of the reviewing tasks of scientists jeopardize what we regard as free academic activity? To some extent it probably would. Is that what it takes for academia to regain control of the activity of scholarly publishing? We believe that the reviewing process represents the most powerful weapon to make the publishing houses understand that they are here to serve the academics and the society, not the other way round.